Research Trends on Deep Learning for Mathematics Learning in Scopus Database: Concept Map & Emerging Themes Using Scopus AI - Zafrullah Zafrullah; Lovieanta Arriza; Salman Rashid; James Leonard Mwakapemba; Mariano Dos Santos; Usama Rasheed (Penerbit Hellow Pustaka, 2025)
This paper aims to explore the concepts and themes emerging in the literature related to